2019
DOI: 10.3390/f10030256
|View full text |Cite
|
Sign up to set email alerts
|

Leaf Fresh Weight Versus Dry Weight: Which is Better for Describing the Scaling Relationship between Leaf Biomass and Leaf Area for Broad-Leaved Plants?

Abstract: Leaf dry mass per unit area (LMA) is considered to represent the photosynthetic capacity, which actually implies a hypothesis that foliar water mass (leaf fresh weight minus leaf dry weight) is proportional to leaf dry weight during leaf growth. However, relevant studies demonstrated that foliar water mass disproportionately increases with increasing leaf dry weight. Although scaling relationships of leaf dry weight vs. leaf area for many plants were investigated, few studies compared the scaling relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
94
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 43 publications
8
94
1
4
Order By: Relevance
“…Leaf shape appears to be an important factor even when data from different species are pooled. For example, a previous study shows that the scaling exponent of leaf fresh mass vs. area is 1.147 for the pooled data of 11 bamboo species (r 2 = 0.99, Lin et al 2018; see also Huang et al 2019). This finding can be explained by the fact that all bamboo plants have a similar leaf shape regardless of the differences in the quotients of leaf width and length (Shi et al 2018(Shi et al , 2019b.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Leaf shape appears to be an important factor even when data from different species are pooled. For example, a previous study shows that the scaling exponent of leaf fresh mass vs. area is 1.147 for the pooled data of 11 bamboo species (r 2 = 0.99, Lin et al 2018; see also Huang et al 2019). This finding can be explained by the fact that all bamboo plants have a similar leaf shape regardless of the differences in the quotients of leaf width and length (Shi et al 2018(Shi et al , 2019b.…”
Section: Discussionmentioning
confidence: 89%
“…If the increase in surface area is proportional to that of dry mass (which means that the scaling exponent of leaf dry mass vs. area is equal to unity), LMA is a constant. However, numerous data sets have demonstrated that leaf area, on average, fails to keep pace with leaf mass for many broad-leaved species (Milla and Reich 2007;Niklas et al 2007;Huang et al 2019), i.e., the scaling exponent for leaf surface area vs. dry mass is less than 1.0. This phenomenon has been referred to as "diminishing returns" (Niklas et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Drier soils have been demonstrated to significantly increase the total biomass of invasive species, whereas, the native species are unaffected by the soil water status [31]. Invasive plant can adjust the resource allocation to leaf, which can decrease leaf are to reduce transpiration loss [32]. However, the relative growth rate of invasive Lantana camara decreased under drought condition; thus, limiting its invasion into arid and sub-arid environments [33].…”
Section: Introductionmentioning
confidence: 99%
“…Fresh biomass was used as proxy for measuring herbicide resistance because the fresh biomass was able to reflect the physiological functions of leaves associated with photosynthesis and respiration better than dry biomass . ALS‐inhibitor herbicides showed variable control in efficacy for all four brome species tested particularly in A. sterilis (Fig.…”
Section: Resultsmentioning
confidence: 99%